Age-related changes in ocular mucosal tolerance: Lessons learned from gut and respiratory tract immunity - Galletti, Jeremías Gastón (2021)
The ocular surface is the part of the visual system directly exposed to the environment, and it comprises the cornea, the first refractive tissue layer and its surrounding structures. The ocular surface has evolved to keep the cornea smooth and wet, a prerequisite for proper sight, and also protected. To this aim, the ocular surface is a bona fide mucosal niche with an immune system capable of fighting against dangerous pathogens. However, due to the potential harmful effects of uncontrolled inflammation, the ocular surface has several mechanisms to keep the immune response in check. Specifically, the ocular surface is maintained inflammation-free and functional by a particular form of peripheral tolerance known as mucosal tolerance, markedly different from the immune privilege of intraocular structures. Remarkably, conjunctival tolerance is akin to the oral and respiratory tolerance mechanisms found in the gut and airways, respectively. And also similarly, this form of immunoregulation in the eye is affected by ageing just as it is in the digestive and respiratory tracts. With ageing comes an increased prevalence of immune-based ocular surface disorders, which could be related to an age-related impairment of conjunctival tolerance. The purpose of this review was to summarize the present knowledge of ocular mucosal tolerance and how it is affected by the ageing process in the light of the current literature on mucosal immunoregulation of the gut and airways.